Half‐Heusler superlattices as model systems for nanostructured thermoelectrics. Issue 3 (11th December 2015) - Komar, Paulina; Jaeger, Tino; Euler, Christoph; Chávez Angel, Emigdio; Kolb, Ute; Müller, Mathis M.; Balke, Benjamin; Aguirre, Myriam Haydee; Populoh, Sascha; Weidenkaff, Anke; Jakob, Gerhard
Abstract: The efficiency of thermoelectric materials is directly related to the dimensionless figure of merit ZT = S 2 σ κ T, therefore, one of the means to improve ZT is to reduce the thermal conductivity. Our research focuses on half‐Heusler superlattices (SLs) and the relationship between the SL period and the thermal conductivity. The cross‐plane thermal conductivity of DC‐sputtered TiNiSn/HfNiSn SLs was measured by the 3 ω method at room temperature and a clear reduction of κ was achieved for all SL periods, in particular for periods smaller than 20 nm. Moreover, the thermal conductivities of TiNiSn and HfNiSn single films display reduced values compared to the literature data for bulk materials. Furthermore, we also found that the quality of interfaces has an influence on κ, namely, SLs with rougher interfaces exhibit an about 20% lower thermal conductivity compared to samples with sharp interfaces.